SINKRONISASI PERMENDAGRI DAN UNDANG-UNDANG PERKAWINAN TERHADAP PENERBITAN KARTU KELUARGA BAGI PASANGAN NIKAH SIRI - M. Adib Hamzawi; Hana Miftakhur Rochmah (Institut Agama Islam Hasanuddin Pare, 2023)
ABSTRACT This study aims to reveal how the procedure for family cards underhand marriage according to the Minister of Home Affairs Regulation and how to synchronize between the Permendagri regulations and the Marriage Law. This research uses library research methods or library research with a normative juridical approach. The results of the study concluded that the process and procedures for couples who marry under the hand/siri according to the Regulation of the Minister of Home Affairs Based on Article 34 of Presidential Regulation No. 96 of 2018 concerning Requirements and Procedures for Registration of Occupation and Civil Registration, then you can attach a Letter of Absolute Responsibility (STJM) for the correctness of data known by 2 (two) witnesses, it can be made by the community based on two reasons, namely, not having birth certificate and or do not have a marriage book/quotation of marriage certificate or other valid evidence, but the relationship status on the Family Card shows that they are husband and wife. Law Number 1 of 1974 concerning Marriage Article 2 paragraph 2 and Regulation of the Minister of Home Affairs Number 108 of 2019 concerning Blank Family Cards, Registers and Citations of Civil Registration Deeds have conflicts of norms between vertical level regulations. Thus, in order to provide legal certainty to the public, Minister of Home Affairs Regulation Number 108 of 2019 concerning Blank Family Cards, Registers and Citations of Civil Registration Deeds must be subject to a judicial review or find an alternative way by considering matters so that no party feel disadvantaged by the existence of these regulations and do not affect other administrative terms and conditions. Keywords : Synchronization, Laws and Regulations, Issuance of Family Card.